Comprehensive safety profile of dipeptidyl peptidase-4 inhibitors: a post-marketing study based on FAERS database using signal detection algorithms - Yoosuf, Beema T; Favas KT, Muhammed; Dutta, Pinaki; Bansal, Dipika (Expert opinion on drug safety, 2024)
Dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) have acquired a foothold in managing type 2 diabetes mellitus, but few concerns have arisen regarding their overall safety profile. The aim of this study is to assess the potential risk of DPP-4 inhibitors by analyzing data from the FDA Adverse Event Reporting System (FAERS) database. This is a retrospective study which explored the FAERS database till March 2023 for the collection of safety reports. The disproportionality analysis was performed using signal detection algorithms (SDAs) incorporating frequentist-based data mining approach such as relative reporting ratio (RRR), reporting odds ratio (ROR) and proportional reporting ratio (PRR) with 95% confidence interval (CI). A total of 14,573 adverse event reports were reported in the FAERS public dashboard associated with all the included DPP-4 inhibitors. The computed PRR, ROR, and RRR indicated positive signals for DPP-4 inhibitors with cardiac failure, pancreatitis, pemphigoid, hypoglycemia, acute kidney injury and lactic acidosis. Saxagliptin showed a higher signal score for cardiac failure, while sitagliptin was more associated with pancreatitis. Moreover, alogliptin exhibited an elevated signal score associated with pancreatic carcinoma. Several significant disproportionality signals were observed with DPP-4 inhibitors. However, clinicians have to consider the comorbidities and concomitant drugs while prescribing these drugs.